A prática do stretching global ativo para otimização da força e prevenção de lesões em esportes de combate - Almeida Júnior, Heleno (2017)
The objective was to analyze Global Active Stretching (GAS) practice concerning strength enhancement and injury prevention support in combat sports, it was inspected the effect of regular GAS practice on the performance of judo practioners, in physical tests and analysed the GAS effect in supporting the maintenance and restitution of normal values of upper limbs thermal asymmetry in jiu-jitsu practioners. The sample for these studies was composed by 12 judo practioners, for the period of 10 weeks and 18 jiu-jitsu practioners for the period of three consecutive days. They were separated into experimental group and control group. For judo practioners, the results show that the regular practice of GAS optimized the flexibility gain and vertical jump, with a gain of 3.00 ± (1.09) cm and 2.49 ± (0.63) cm respectively, and did not reflect on the results of the other tests. For jiu-jitsu practioners, the regular practice of GAS enhanced the healing process for the forearm area after competition, decrease in the ΔTP (°C) of 0.18°C. Therefore the regular practice of GAS increases the flexibility of back chain and the performance in vertical jump CMJ, for judo practioners, and does not interfere at the maintenance of normality of thermal , for contralateral upper limbs areas, in jiu jitsu athletes being able to restore normal values of thermal asymmetry in the forearm posterior region.